A synopsis of Ocotea (Lauraceae) from the Reserva Natural Vale, Linhares, Espírito Santo, Brazil - de Moraes, Pedro Luís Rodrigues [UNESP]; Vergne, Matheus Carvalho [UNESP] (Wiley, 2019)
In the first treatment of this series, twenty-one species of 12 genera of Lauraceae (excluding Ocotea) were reported for the Reserva Natural Vale. In the present treatment, thirty-two species of Ocotea are reported from the area. Descriptions, an identification key, commentary and illustrations of the species are presented. Pistillate flowers of Ocotea aniboides and O. kostermansiana are described for the first time, and lectotypes are designated for six names: Aydendron nitidum, Ocotea glaziovii, O. kostermansiana, Oreodaphne maranhana, Oreodaphne pallida, and Oreodaphne spectabilis.
Keywords: Atlantic rainforest; Laurales; Neotropics; taxonomy